2007
DOI: 10.1159/000096939
|View full text |Cite
|
Sign up to set email alerts
|

Acute Scrotal Pain in Children – Ten Years’ Experience

Abstract: Introduction: Acute scrotal pain sometimes requires prompt surgical intervention and therefore accurate diagnosis of different etiologies of acute scrotal pain has great therapeutical and prognostic significance. The aim of this study was to analyze the incidence, symptomatology and results of treatment of acute scrotal pain in children. Material and Method: The study included patients hospitalized at the Pediatric Surgery Clinic with a diagnosis of acute scrotal pain. We retrospectively analyzed anamnestic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 31 publications
0
24
0
2
Order By: Relevance
“…In our hospital, ultrasound with an expert sonologist, is only available during day time and not during the late afternoon and at night. As pain and swelling of scrotum are the most common symptoms in testicular torsion and also there are paucity of diagnostic tools, so some studies suggest early surgical exploration [15][16][17] , as we have done this for the indicated patients in our study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our hospital, ultrasound with an expert sonologist, is only available during day time and not during the late afternoon and at night. As pain and swelling of scrotum are the most common symptoms in testicular torsion and also there are paucity of diagnostic tools, so some studies suggest early surgical exploration [15][16][17] , as we have done this for the indicated patients in our study.…”
Section: Discussionmentioning
confidence: 98%
“…Acute pediatric scrotal pain sometimes requires prompt surgical intervention and therefore accurate diagnosis of different etiologies of acute scrotal pain has great therapeutic and prognostic significance 1 …”
Section: Introductionmentioning
confidence: 99%
“…Akut skrotal ağrı nedenleri arasında; akut epididimit (%43), testiküler apandiks torsiyonu (%40,6), testis torsiyonu (%11,7) ve diğer nedenler (%4,7) yer almaktadır (6). Epididimorşitin etiyolojisinde kabakulak virüsü, Escherichia coli, Klebsiella pneumonia, Staphylococcus aureus ve streptokoklar rol oynamaktadır.…”
Section: Discussionunclassified
“…Torsion of testicular appendix, testicular torsion and acute epididymitis (AE) have been shown to be the major differential diagnoses in several cohorts. [1][2][3][4] The management of each patient depends on the individual clinical manifestations, laboratory and sonographic findings. Although it has been shown that colour Doppler sonography can identify testicular torsion in boys reliably, 5 the surgical exploration remains the gold standard diagnostic tool so as to maximise the chances of testicular salvage in case of testicular torsion.…”
mentioning
confidence: 99%
“…In different series it ranges from 3.7% to 71% of children presenting with acute scrotum. [1][2][3][4][5][6][7][8] A bimodal age distribution of epididymitis has been reported in many series, with peak incidence in infancy and mainly the age group of 10-12 years. [7][8][9][10] In our district hospital we encountered six consecutive cases of AE in prepubertal boys over a period of two months.…”
mentioning
confidence: 99%